The impact of globalization in Muslim world on family values: a case of Malaysia - Abd Rahman, Saodah (2017)
Abstract: Globalization promotes the integration of socio-cultural, political and economic systems of nations into global ones. Sociologists consider this process as cultural and intellectual assimilation. Numerous studies, in this context, have been conducted and highlighted the nature of globalization and its positive and negative impacts on society. The significant point is the changes that globalization initiated are not in accord with the intellectual and ideological bases of Muslim societies. The purpose of this study is to explore the social issues and social relations that are affected by the process of globalization. This study will assess the changes that are taking place in interpersonal relation as well as in the institution of family. The present study is based on previous literatures and documents analysis. Family plays an important role in the life of an individual and in society as well. As such this study highlights how family relations and social values are undergoing change under the process of globalization in Muslim societies. It will also assess the impact of globalization on transformation of individual preferences and social values. The authors argue that globalization affected Islamic values and made Muslims more materialistic, while the history of Muslim societies indicated that individual preferences and social values were based on religious ethos. Suggestions will be made about how Muslim societies can get rid of the discursive and unhealthy impact of globalization on the Muslim world.